Insulin Like Growth Factor Binding Protein 7 as a Novel Diagnostic Marker in Sera of Iraqi Patients with Acromegaly - Layla Othman Farhan; Baydaa Ahmed Abed; Kashtl Ghasaq J.; Isam Noori Salman (مجلة بغداد للعلوم)
The purpose of this study was to measure serum levels of insulin-like growth factor-binding protein (IGFBP7), Insulin-like Growth Factor 1 (IGF-1), Growth Hormone (GH), Interleukin 6 (IL-6) and insulin in acromegaly patients and healthy controls. The acromegaly group had 60 patients, while the population group had 30 people who had never had acromegaly before. The concentration of IGFBP7, IGF-1, GH, IL-6, and insulin were determined. The results of the present study indicate that IGFBP7 level in the acromegaly group was significantly lower (1.690.07 ng/mL vs. 2.740.12 ng/mL, respectively, p = 0.001). IGF-1, GH, IL-6, and insulin concentrations were also significantly higher in acromegaly patients. The diagnostic accuracy (2.194) was excellent in separating acromegaly from the healthy patient group, and the area under the curve (AUC = 0.871, p = 0.001). From the results of the present study, we can conclude that serum IGFBP7 can be used to distinguish acromegaly patients from healthy individuals.